Essential Fatty Acid Assimilation and Synthesis in Larvae of the Bivalve Crassostrea gigas. Issue 5 (13th March 2015) - da Costa, Fiz; Robert, René; Quéré, Claudie; Wikfors, Gary H.; Soudant, Philippe
Abstract: Essential fatty acids (EFA) are important for bivalve larval survival and growth. The purpose of this study was to quantitatively assess for the first time through a mass‐balance approach dietary EFA incorporation and synthesis within Crassostrea gigas larvae. A first experiment was carried out using two microalgae, Tisochrysis lutea (T) and Chaetoceros neogracile (Cg), as mono‐ and bi‐specific diets. A second experiment using a similar design was performed to confirm and extend the results obtained in the first. Flow‐through larval rearing was used for accurate control of food supply and measurement of ingestion. Non‐methylene‐interrupted fatty acids were synthetized from precursors supplied in the diet: 16:1n‐7 and 18:1n‐9, mediated by Δ5 desaturase. Moreover, this Δ5 desaturase presumably allowed larvae to convert 20:3n‐6 and 20:4n‐3 to 20:4n‐6 and 20:5n‐3, respectively, when the product EFA were poorly or not supplied in the diet, as when larvae were fed T exclusively. Under our experimental conditions, none of the diets induced 22:6n‐3 synthesis; however, 22:6n‐3 incorporation into larval tissues occurred selectively under non‐limiting dietary supply to maintain optimal levels in the larvae. This combination of flow‐through larval rearing and biochemical analysis of FA levels could be applied to additional dietary experiments to precisely define optimal levels of EFA supply.